Multi-messenger astrophysics of black holes and neutron stars as probed by ground-based gravitational wave detectors: from present to future - Corsi, Alessandra; Barsotti, Lisa; Berti, Emanuele; Evans, Matthew; Gupta, Ish; Kritos, Konstantinos; Kuns, Kevin; Nitz, Alexander H.; Owen, Benjamin J.; Rajbhandari, Binod; Read, Jocelyn; Sathyaprakash, Bangalore S.; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The ground-based gravitational wave (GW) detectors LIGO and Virgo have enabled the birth of multi-messenger GW astronomy via the detection of GWs from merging stellar-mass black holes (BHs) and neutron stars (NSs). GW170817, the first binary NS merger detected in GWs and all bands of the electromagnetic spectrum, is an outstanding example of the impact that GW discoveries can have on multi-messenger astronomy. Yet, GW170817 is only one of the many and varied multi-messenger sources that can be unveiled using ground-based GW detectors. In this contribution, we summarize key open questions in the astrophysics of stellar-mass BHs and NSs that can be answered using current and future-generation ground-based GW detectors, and highlight the potential for new multi-messenger discoveries ahead.